The quiet revolution in India's food supply chains - Reardon, Thomas; Minten, Bart (International Food Policy Research Institute, 2011)
There has been a rapid transformation of food supply chains in India over the past two decades. Modern retail sales are growing at 49 percent per year and quickly penetrating urban food markets and even rural markets. The food-processing sector is growing quickly while also concentrating and undergoing a rapid increase in the capital-output ratio, with little increase in employment. A modern segment is emerging in the wholesale sector, with the penetration of modern logistics firms and specialized modern wholesalers.